Potential of Using Walnuts as a Part of Nutritional Therapy for Inflammatory Bowel Diseases - Andrew V. Nalyotov; Anatoly I. Khavkin; Alexander N. Matsynin; Vera S. Strionova (Педиатрическая фармакология, 2025)
Walnuts are major component of Mediterranean and Asian diets and are increasingly used in different diets around the world due to their confirmed nutritional and health benefits. Walnuts’ components are abundant with omega-3 polyunsaturated fatty acids, essential amino acids, vitamins, polyphenols, phytosterols, and other nutrients and biologically active compounds with antioxidant, anti-inflammatory and immunomodulating properties. Walnuts currently have demonstrated promising effect in inflammatory bowel diseases management. This study presents key mechanisms underlying walnuts’ therapeutic potential in inflammatory bowel diseases management, such as modulation of intestinal mucosa permeability, inflammatory processes regulation, oxidative stress reduction, and gut microbiota composition correction.